Potential nutrition contributions to exercise associated muscle cramping: a case study approach - Dole, Andrew (Kansas State University, 2019)
Beliefs regarding the role of electrolytes and hydration in exercise associated muscle cramping (EAMC) may be hindering meaningful nutrition-based improvements and prevention strategies. There is a need to explore the role of carbohydrate, energy availability, exertion level, electrolyte status, and hydration status in combination with the emerging nervous system fatigue research to assess the role of these possible predictors of EAMC. However, these factors vary dramatically between individual athletes, and prior to assessing the role of possible predictors of EAMC, the nutrition and hydration practices, the individual responses to competition, and the history of EAMC in endurance athletes must first be better characterized. To achieve this, a case study approach was used to capture pre-race and on course food and beverage intake, pre and post-race body weight, relative perceived effort, and history of EAMC for four recreational runners. Carbohydrate, energy availability, and hydration status varied across cases with one occurrence of EAMC. Reported pre-race CHO intake for all but one participant fell below 5 g/kg/day. Two of the four runners reported a history of EAMC, one of which experienced EAMC during the race. The two participants with a prior history of EAMC, also reported the lowest energy and CHO intakes. The one participant who experienced an EAMC reported a history of prior EAMC, experienced the greatest body mass loss, experienced the greatest estimated sodium loss, and reported suboptimal energy and CHO intakes. While this observed case of EAMC does not appear to be inconsistent with the traditional dehydration/ electrolyte loss theory, it also generates questions regarding the potential contribution of suboptimal energy and CHO intakes. Overall, this study presents an in-depth perspective for four recreational runners. An improved understanding of the nutrition and hydration practices of endurance athletes along with an enhanced appreciation of the unique nature of each athlete’s responses can benefit professionals who work with athletes and can serve to generate vital research questions related to the role nutrition and hydration play in the occurrence of EAMC.
Keywords: EAMC; Electrolyte; Cramping; Hydration; Nutrition; Endurance